2001
DOI: 10.1038/sj.ijo.0801582
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of waist circumference, waist-to-hip ratio and body mass index as indicators of cardiovascular risk factors. The Canadian Heart Health Surveys

Abstract: OBJECTIVE:To comparatively evaluate cut-off points of waist circumference, body mass index and waist to hip ratio with respect to their ability to predict other individual and multiple cardiovascular disease risk factors. DESIGN: Population-based, cross-sectional surveys. SUBJECTS: A total of 9913 men and women aged 18 ± 74, selected using health insurance registries from ®ve Canadian provinces. MEASUREMENTS: Anthropometric measures, other cardiovascular risk factors, receiver operating characteristic curves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
285
6
18

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(335 citation statements)
references
References 24 publications
(20 reference statements)
22
285
6
18
Order By: Relevance
“…In women, younger adults and those with more prevalent risk factors such as dyslipidemia, lower cutoff points are more appropriate, whereas in older age groups and those with less-prevalent risk factors such as multiple risk factors (as a surrogate for incident CVD), higher values are more suitable. 13,33 In this study, overall predictive discrimination (as judged by AUC) for incident CVD was better for WHR, WHtR and WC than BMI in both genders aged o60 years; however, there was no difference in the predictive power of anthropometric variables in either genders aged 460 years, a finding that is similar to other studies. 34,35 Harris et al 35 highlighted that in older men and women, WC and BMI were more closely related to total body fat than visceral fat; hence, central obesity variables, which include subcutaneous fat, in older population may not be related to CVD events as the same degree as in the middle-aged population.…”
Section: Obesity Variables To Predict Cardiovascular Events F Hadaeghsupporting
confidence: 87%
“…In women, younger adults and those with more prevalent risk factors such as dyslipidemia, lower cutoff points are more appropriate, whereas in older age groups and those with less-prevalent risk factors such as multiple risk factors (as a surrogate for incident CVD), higher values are more suitable. 13,33 In this study, overall predictive discrimination (as judged by AUC) for incident CVD was better for WHR, WHtR and WC than BMI in both genders aged o60 years; however, there was no difference in the predictive power of anthropometric variables in either genders aged 460 years, a finding that is similar to other studies. 34,35 Harris et al 35 highlighted that in older men and women, WC and BMI were more closely related to total body fat than visceral fat; hence, central obesity variables, which include subcutaneous fat, in older population may not be related to CVD events as the same degree as in the middle-aged population.…”
Section: Obesity Variables To Predict Cardiovascular Events F Hadaeghsupporting
confidence: 87%
“…Subjects were instructed to continue their regular diet and exercise patterns. They also received instructions on how to properly complete the daily dietary intake record; and they were asked to complete these records on 2 occasions for periods of 3 days (days 1-3 and days [40][41][42]. The records were analyzed by Food Processor (Salem, Oregon).…”
Section: Study Protocolmentioning
confidence: 99%
“…In addition to the assessment of the potential for this product to aid in body weight loss of obese subjects, the influence of this nutraceutical on upper abdominal, waist, and hip circumference; heart rate; and blood pressure was investigated. Waist circumference and body fat percentage were of particular interest because some reports [34][35][36][37][38][39][40][41][42][43] indicate that they are better predictors of cardiovascular disease than either body mass index (BMI) or waist-to-hip ratio.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that 'optimal' WC thresholds for predicting future coronary risk may differ from the single thresholds. An ROC analysis of the CHHS (Dobbelsteyn et al, 2001) demonstrated that thresholds of 80 cm (F)/90 cm (M) provided the best balance between sensitivity and specificity in predicting the presence of Z2 CVD risk factors. Recently, it was shown that specific WC thresholds within BMI categories could improve the identification of individuals at high risk of future coronary events over a single WC cutoff (Ardern et al, 2004).…”
Section: Discussionmentioning
confidence: 99%